Salvia ramamoorthyana and S. omissa (Lamiaceae), two names for two old and largely confused species from Mexico - González-Gallegos, Jesús Guadalupe (Phytotaxa, 2015)
Bentham, G. (1832–1836) Labiatarum genera et species. Ridgeway, London, 783 pp. Bentham, G. (1848) Labiatae. In: Candolle, A. de (Ed.) Prodromus Systematis Naturalis Regni Vegetabilis. Victor Masson, Paris, pp. 27–603. Briquet, J. (1898) Fragmenta monographiea Labiatarum, fasciculus V, observations sur quelques Labiées intéressantes ou nouvelles principalement de L’Herbier Delessert. Annuaire du Conservatoire et du jardins botaniques de Genève 2: 102–251. Cornejo-Tenorio, G. & Ibarra-Manríquez, G. (2011) Diversidad y distribución del género Salvia (Lamiaceae) en Michoacán, México. Revista Mexicana de Biodiversidad 82: 1279–1296. Epling, C. (1939) A revision of Salvia subgenus Calosphace. Feddes Repertorium Specierum Novarum Regni Vegetabilis 110: 1–383. Epling, C. (1940) Supplementary notes on American Labiatae. Bulletin of the Torrey Botanical Club 67: 509–534. http://dx.doi.org/10.2307/2480972 Epling, C. (1941) Supplementary notes on American Labiatae-II. Bulletin of the Torrey Botanical Club 68: 552–568. http://dx.doi.org/10.2307/2481456 Epling, C. (1944) Supplementary notes on American Labiataae-III. Bulletin of the Torrey Botanical Club 71: 484–497. http://dx.doi.org/10.2307/2481241 Epling, C. (1947) Supplementary notes on American Labiatae-IV. Bulletin of the Torrey Botanical Club 74: 512–518. http://dx.doi.org/10.2307/2481876 Epling, C. (1951) Supplementary notes on American Labiatae-V. Brittonia 7: 129–142. http://dx.doi.org/10.2307/2804702 Epling, C. (1960) Supplementary notes on American Labiatae-VII. Brittonia 12: 140–150. http://dx.doi.org/10.2307/2805214 Epling, C. & Játiva, C. (1963) Supplementary notes on American Labiatae-VIII. Brittonia 15: 366–376. http://dx.doi.org/10.2307/2805381 Epling, C. & Játiva, C. (1966) Supplementary notes on American Labiatae-IX. Brittonia 18: 255–265. http://dx.doi.org/10.2307/2805366 Epling, C. & Játiva, C. (1968) Supplementary notes on American Labiatae-X. Brittonia 20: 295–313. http://dx.doi.org/10.2307/2805687 Epling, C. & Mathias, M.E. (1957) Supplementary notes on American Labiatae-VI. Brittonia 8: 297–313. http://dx.doi.org/10.2307/2804980 Espejo Serna, A. & Ramamoorthy, T.P. (1993) Revisión taxonómica de Salvia sección Sigmoideae (Lamiaceae). Acta Botanica Mexicana 23: 65–102. Fernald, M.L. (1900) A synopsis of the Mexican and Central American species of Salvia. Contributions from the Gray Herbarium of Harvard University 19: 490–556. http://dx.doi.org/10.2307/25129966 González-Gallegos, J.G. & Castro-Castro, A. (2013) New insights on Salvia platyphylla (Lamiaceae) and description of S. pugana and S. albiterrarum, two new species from Jalisco, Mexico. Phytotaxa 93 (2): 47–60. http://dx.doi.org/10.11646/phytotaxa.93.2.1 González-Gallegos, J.G. & Gama-Villanueva, O.J. (2013) Resurrection of Salvia species (Lamiaceae) recently synonymized in Flora Mesoamericana. Phytotaxa 151 (1): 1–24. http://dx.doi.org/10.11646/phytotaxa.151.1.1 González-Gallegos, J.G., Vázquez-García, J.A. & Cházaro-Basáñez, M.J. (2013) Salvia carreyesii, Salvia ibugana and Salvia ramirezii (Lamiaceae), three new species from Jalisco, Mexico. Revista Mexicana de Biodiversidad 84: 7–19. http://dx.doi.org/10.7550/rmb.29131 Hemsley, W.B. (1881–1882) Botany vol. II. In: Godman, D. & Salvin, O. (Eds.) Biologia centrali-americana. R. H. Porter and Dulau & Co., London, pp. 621. Jenks, A.A., Walker, J.B. & Kim, S.-C. (2013) Phylogeny of New World Salvia subgenus Calosphace (Lamiaceae) based on cpDNA (psbA-trnH) and nrDNA (ITS) sequence data. Journal of Plant Research 126: 483–496. http://dx.doi.org/10.1007/s10265-012-0543-1 Klitgaard, B. (2012) Salvia L. In: Davidse, G., Sousa, -S.M., Knapp, S. & Chiang, F. (Eds.) Flora Mesoamericana 4(2), Rubiaceae a Verbenaceae. Missouri Botanical Press, St. Louis, pp. 396–424. Kunth, C.S. (1817) Nova genera et species plantarum. The Greek-Latin-Germanic Library, Paris, 404 pp. Linnaeus, C. (1753) Species plantarum. Salvius, Stockholm, 1200 pp. McNeill, J., Barrie, F.R., Buck, W.R., Demoulin, V., Greuter, W., Hawksworth, D.L., Herendeen, P.S., Knapp, S., Marhold, K., Prado, J., Prud’Homme Van Reine, W.F., Smith, G.F., Wiersema, J.H. & Turland, N.J. (2012) International Code of Nomenclature for algae, fungi, and plants (Melbourne Code) adopted by the Eighteenth International Botanical Congress Melbourne, Australia, July 2011. [Regnum Vegetabile 154]. Gantner, Ruggell, 240 pp. Ortega, C.G. de (1797) Novarum aut rariorum plantarum horti reg. botan. Matrit. Ibarriana, Madrid, 51 pp. Rodríguez-Jiménez, L.S. & Espinosa-Garduño, J. (1996) Listado florístico del estado de Michoacán sección III (Angiospermae: Connaraceae-Myrtaceae except Fagaceae, Gramineae, Krameriaceae y Leguminosae). Flora del Bajío y de Regiones Adyacentes, Fascículo Complementario 10: 1–296. Tropicos (Org.) (2015) Tropicos database, Missouri Botanical Garden, St. Louis. Available from: http://www.tropicos.org/Name/17606846 (accessed 25 June 2015)